A Revised Perspective on the Evolution of Troponin I and Troponin T Gene Families in Vertebrates. (15th December 2022) - Joyce, William; Ripley, Daniel M; Gillis, Todd; Black, Amanda Coward; Shiels, Holly A; Hoffmann, Federico G
Abstract: The troponin (Tn) complex, responsible for the Ca 2+ activation of striated muscle, is composed of three interacting protein subunits: TnC, TnI, and TnT, encoded by TNNC, TNNI, and TNNT genes. TNNI and TNNT are sister gene families, and in mammals the three TNNI paralogs ( TNNI1, TNNI2, TNNI3 ), which encode proteins with tissue-specific expression, are each in close genomic proximity with one of the three TNNT paralogs ( TNNT2, TNNT3, TNNT1, respectively). It has been widely presumed that all vertebrates broadly possess genes of these same three classes, although earlier work has overlooked jawless fishes (cyclostomes) and cartilaginous fishes (chimeras, rays, and sharks), which are distantly related to other jawed vertebrates. With a new phylogenetic and synteny analysis of a diverse array of vertebrates including these taxonomic groups, we define five distinct TNNI classes ( TNNI1 -5), with TNNI4 and TNNI5 being only present in non-amniote vertebrates and typically found in tandem, and four classes of TNNT ( TNNT1-4 ). These genes are located in four genomic loci that were generated by the 2R whole-genome duplications. TNNI3, encoding "cardiac TnI" in tetrapods, was independently lost in cartilaginous and ray-finned fishes. Instead, ray-finned fishes predominantly express TNNI1 in the heart. TNNI5 is highly expressed in shark hearts and contains a N-terminal extension similar to that of TNNI3 found in tetrapod hearts. Given that TNNI3 and TNNI5 are distantly related, this supports the hypothesis that the N-terminal extension may be an ancestral feature of vertebrate TNNI and not an innovation unique to TNNI3, as has been commonly believed.